Peran Guru TK Arastamar Sengkuang dalam Pendidikan Anak Agar Bisa Menanamkan Karakter Kristen Sejak Dini - Ferdi Eka Darma; Sandra R. Tapilaha (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Early childhood character education is an important foundation in developing a strong and virtuous personality in children. This study aims to examine the role of teachers at Arastamar Sengkuang Kindergarten in instilling Christian character values ​​in young children. Through a contextual and spiritual learning approach, teachers are not only tasked with teaching but also serving as role models in teaching values ​​such as love, honesty, discipline, responsibility, and gratitude. The method used in this study was direct observation of classroom teaching and learning activities, including prayer, singing, storytelling, and guidance for parents. The results of the observations indicate that character values ​​are instilled through positive daily habits, with active support from parents. Cooperation between teachers and parents is a key factor in supporting children's character development, thus having a positive impact on children's behavior. This Community Service Program (PKM) is expected to make a significant contribution to the development of character education in Christian schools. In addition, this study is also expected to strengthen the role of character education in developing a young generation with high integrity and morality. Through this program, children are expected to grow into individuals who are not only academically intelligent but also possess good personalities. This program is also expected to be an example for other educational institutions in instilling character values ​​from an early age.